Should GPs have direct access to imaging for headache? A qualitative study of patients’ views in the UK - Raphael Underwood; Gabriella Wojewodka; Asif Mazumder; Rachael Kilner; Leone Ridsdale (BMJ Open)
Objective We aimed to describe patients’ views of a new referral pathway of general practitioner (GP) direct access to MRI, versus imaging after referral to a specialist.Design This qualitative study involved 20 semistructured interviews. Twenty patients (10 from each pathway) were purposively recruited and interviewed to describe their attitudes.Setting A neurology headache clinic and neuroradiology services from the boroughs of Southwark and Lambeth in South London, UK.Participants Twenty patients were involved in this study.Results Over half of the participants felt relieved once they received their scan results, while some remained uncertain about the underlying cause of their symptoms. Some participants described a long wait to see a specialist. Others described a long wait time to receive scan results, especially from their GP. Spontaneous reduction in headache symptoms occurred for some participants and for others, normal imaging results allowed them to focus more on symptom management.Conclusion Relief was reported especially when scan results had been explained clearly and without too much delay. Those with continuing pain focused on how to get relief from symptoms. Patient experience might be improved with clearer information from GPs about how patients can access results, standard reporting procedures and closer liaison between neuroradiology and GPs.